PENGARUH INTELLECTUAL CAPITALTERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN CORPORATE GOVERNANCESEBAGAI VARIABEL MODERASI: Studi Kasus Pada Perusahaan Manufaktur Sektor Aneka Industri DiBursa Efek Indonesia Periode 2017-201 (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
Intellectual capital is the sum of what is produced by three main things in an organization, namely capital employed, human capital and structural capital which are related to knowledge and technology to provide added value for the company in the form of competitive advantage. This research aims to analyze "The Influence of Intellectual Capital on Company Financial Performance with Corporate Governance as a Moderating Variable". This research uses quantitative data with secondary data sources. The data collection techniques used in this research are literature study and documentation. The sample used used a purposive sampling technique, totaling 9 companies. Based on data analysis from the t test results, VACA, VAHU and VAICTM have a significant effect on ROE. Meanwhile, VAHU and Intellectual Capital, which are moderated by corporate governance, which is proxied by institutional ownership, show no effect on ROE.